2016
DOI: 10.1007/s10461-016-1458-y
|View full text |Cite
|
Sign up to set email alerts
|

Experiences with HPTN 067/ADAPT Study-Provided Open-Label PrEP Among Women in Cape Town: Facilitators and Barriers Within a Mutuality Framework

Abstract: Placebo-controlled trials of pre-exposure prophylaxis (PrEP) have reported challenges with study-product uptake and use, with the greatest challenges reported in studies with young women in sub-Saharan Africa. We conducted a qualitative sub-study to explore experiences with open-label PrEP among young women in Cape Town, South Africa participating in HTPN 067/Alternative Dosing to Augment Pre-Exposure Prophylaxis Pill Taking (ADAPT). HPTN 067/ADAPT provided open label oral FTC/TDF PrEP to young women in Cape T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
98
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(109 citation statements)
references
References 37 publications
(35 reference statements)
7
98
0
1
Order By: Relevance
“…These findings align with previous research that uncovered how collectivization surrounding interventions (structural, bio-medical, behavioural) shape community identities and collective security strategies [36]. Furthermore, qualitative research on PrEP use in Sub-Sahara Africa found that women placed a high level of importance on contributing to the well-being of their community [37]. Our findings point to the importance of situating PrEP scale-up within the trusted spaces of community-based organizations as a means of supporting PrEP uptake and adherence.…”
Section: Discussionsupporting
confidence: 86%
“…These findings align with previous research that uncovered how collectivization surrounding interventions (structural, bio-medical, behavioural) shape community identities and collective security strategies [36]. Furthermore, qualitative research on PrEP use in Sub-Sahara Africa found that women placed a high level of importance on contributing to the well-being of their community [37]. Our findings point to the importance of situating PrEP scale-up within the trusted spaces of community-based organizations as a means of supporting PrEP uptake and adherence.…”
Section: Discussionsupporting
confidence: 86%
“…The difficulty for women in adhering to the post-sex dose in our study was confirmed by qualitative data. 24 Pre-sex and post-sex dosing of a vaginal gel was effective in CAPRISA 004, 25 although this finding was not replicated in the FACTS 001 trial. 26 At the time that the HPTN 067/ADAPT study was being implemented, only daily dosing of PrEP had evidence for efficacy, as described in information provided to participants.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, training providers to counsel about the benefits and risks is key to wide-scale implementation of PrEP, particularly in the context of combination HIV prevention. Although medical or research mistrust emerged as a less common theme in our study, which was conducted within an implementation study of a PrEP delivery model, as compared with PrEP clinical trials testing product efficacy [13,15,17], local ownership of PrEP implementation should help abate any perceptions of experimentation, racism or neocolonialism.…”
Section: Discussionmentioning
confidence: 99%
“…Barriers include drug-related issues, such as side effects and pill characteristics; logistical issues around drug use, such as timely refills and travel; and social stigma, related to being mistakenly identified as HIV-infected and disclosure of use with sexual partners. Furthermore, clinical trials focused on HIV prevention among women have found that experiences with clinic personnel, mistrust of research, and the influence of male partners can either support or deter study participation and PrEP use [1317]. However, it remains unclear if heterosexual couples participating in an open-label implementation project in resource-limited settings identify similar themes.…”
Section: Introductionmentioning
confidence: 99%